Migrating to Swift from Android - Liao, Sean (Berkeley, CA, New York, NY Apress, Distributed to the Book trade worldwide by Springer, 2014)
In 250 pages, Migrating to Swift from Android gives you?as an experienced Android app developer?all you need to create native iOS apps using the latest Swift programming language. Starting with preparing your Xcode 6 IDE and introducing just enough iOS application framework fundamentals, you'll understand how to create meaningful Swift applications for iOS 8 immediately. After the short IDE setup guide, this book continues by providing guidance on how to translate your existing Android apps to iOS. Every topic comes with a tutorial project; you'll plan and structure your iOS apps following a typical top-down process using Xcode Storyboards. To implement use cases, you'll cover common mobile topics, including user interfaces, managing data, and networking with remote services. As you move through Part 2 of this book, you'll create simple and meaningful iOS apps with rich UI components to handle common CRUD operations locally and remotely. Part 3 demonstrates the whole porting process by translating a typical mobile app from Android to iOS 8 from start to finish. When you finish reading Migrating to Swift from Android, you'll be an iOS developer as well as an Android developer. And, you will be fully convinced you can create iOS apps just like you do in Android. In most cases, it is a waste not to port your native Android apps to iOS.
Optional VariableImplicitly Unwrapped Optionals; Tuples; Collections; Control Flow; Switch; Enumerations; Functions; Class; Property; Method; Reference Type vs. Value Types; iOS Project Anatomy; Xcode Storyboard; Object Library and Attributes Inspector; Summary; Part II: A Roadmap for Porting; Chapter 3: Structure Your App; Model-View- Controller; Content View; Auto Layout; Size Classes; Content View Controller; Pair with Content View; Interact with Content View; UIViewController Life Cycle; viewDidLoad; viewWillAppear; viewDidAppear; viewWillDisappear; viewDidDisappear ()
Includes index
Keywords: Android (Electronic resource) / fast; programmeren; BUSINESS & ECONOMICS / Management Science / bisacsh; BUSINESS & ECONOMICS / Management / bisacsh; Programmation (Informatique); Operating systems (Computers) / http://id.loc.gov/authorities/subjects/sh85094982; programming; computerwetenschappen; computer programming / aat; Mobile computing / fast; Informatie- en communicatietechnologie (algemeen); Information and Communication Technology (General); Computer programming / fast; Systèmes d'exploitation (Ordinateurs); BUSINESS & ECONOMICS / Organizational Behavior / bisacsh; Computer programming / http://id.loc.gov/authorities/subjects/sh85107310; Informatique mobile; operating systems / aat; Apple computer / fast; Mobile computing / http://id.loc.gov/authorities/subjects/sh95004596; Operating systems (Computers) / fast; Apple (Ordinateurs); BUSINESS & ECONOMICS / Industrial Management / bisacsh; Android (Electronic resource) / http://id.loc.gov/authorities/names/n2009043077; computer sciences; Apple computer / http://id.loc.gov/authorities/subjects/sh85006124